Prevalence of stress, anxiety and depression in undergraduate medical students: a cross sectional study - Kamboj, Gaurav; ., Nilika; Bhartiya, Sweta (International Journal Of Community Medicine And Public Health, 2021)
Background: It is important to identify the prevalence and risk factors of psychological distress among medical students which not only affect their health but also the academic achievements at different points of time in their study period. In addition, the patient care is affected by psychological distress among physicians such as poor communication, diminished quality of care and medical errors have been found associated with physical stress. Methods: The present study was a descriptive type of cross-sectional study, which was conducted in a government medical college located in rural Haryana, India from June to July 2018 among 200 MBBS students after adopting inclusion and exclusion criteria. A pre-validated, pre-designed structured depression, anxiety and stress scale-21 items (DASS-21) (annexure 2) was used for obtaining information from the study subjects. The total score of the study subjects was computed and thereafter graded for levels of stress, anxiety and depression. Results: The response rate was 94.5%. The mean score for DASS 21 scale was found to be 16.13 (±11.27). Out of the total, 61.4% students are suffering from different levels of depression. About two-third of the study participants (69.8%) were suffering from different levels of anxiety. The prevalence of stress was about 46.6% in the study subjects. Conclusions: The study confirmed the general impression that there is considerable amount of stress, anxiety and depression in medical students.